Linking Dutch national public services data to estimate the prevalence of intellectual disabilities. (20th October 2021) - Cuypers, M; Tobi, H; Naaldenberg, J; Leusink, GL
Abstract: While people with ID depend on public (health) services more than others, they are difficult to identify within population data. This limits the opportunities to accurately estimate ID prevalence, monitor trends, or to tailor public health interventions according to the needs and characteristics of this groups. By linking relevant databases, this study estimated the prevalence of ID based on public service use, and explored methods to monitor other developments in the ID population. Starting point was the Dutch population register, containing all Dutch adults alive at January 1, 2015. From databases of public services (long-term care, and social benefits) we retrieved information of those individuals who accessed these services with an ID as primary reason. Through this method, 187, 149 unique Dutch adults with an ID were identified within a population of almost 12.7 million Dutch adults, giving an ID prevalence estimate of 1.45%. Prevalence of ID was higher among males (1.7%) than among females (1.2%). Most individuals with ID were identified through use of residential care services (n = 91, 064; 0.7%). Non-residential ID-related care was utilized by 27, 007 individuals (0.2%). Social, employment, or income support due to a (mild) ID was received by 69, 078 individuals (0.5%). Mean age in these ID-groups was between 8 and 10 years younger than in the general Dutch population. ID prevalence declined with increasing age across all ID-groups. The ID prevalence in The Netherlands as determined in this study aligned with international estimates. This suggests that national supportive services are well accessible for people with ID. Moreover, it demonstrated that databases from national supportive services can be a useful source to identify individuals with ID at the population level, and it enables structural monitoring of the ID population through linking national databases.